α,ω-Bis(hydrazidomethylsulfinyl and sulfonyl)alkanes: State in solution and interaction with copper(II) - V.V. Neklyudov; G.A. Boos; M.M. Shulaeva; G.A. Chmutova; R.R. Amirov (Учёные записки Казанского университета: Серия Естественные науки)
In this paper, the results of our previous findings on the solvent, protolytic, and complexing abilities of α,ω-bis(amido- and hydrazidomethylsulfinyl and sulfonyl)alkanes were summarized and compared. In addition, the most probable structures of copper(II) complexes (mononuclear 1:1 and 1:2, binuclear 2:4) with 1,8-bis(hydrazidomethylsulfonyl)octane and 1,10-bis(hydrazidomethylsulfonyl)decane were characterized by DFT at PBE/6-311G(d) level of theory. 1,8-Bis(hydrazidomethylsulfonyl)octane and 1,10-bis(hydrazidomethylsulfonyl)decane were found to have unfolded conformations and to be coordinated by copper(II) in the amide form like hydrazides of carboxylic acids. In the binuclear complex, all four ligands are bridging and differ in coordination ways, exhibiting the denticity of four, two, and three. It was demonstrated that sulfoxide groups do not take part in coordination.